A new perspective for European SMEs' innovative support analysis: Does non-financial support matter? - Gyamfi, Solomon; Gerstlberger, Wolfgang; Prokop, Viktor; Stejskal, Jan (My University, 2024)
Most of the previous research focused on the effects of public support for SMEs' innovative activities dealt with the effects of financial incentives, while non-financial support was considered a kind of "black box". This research therefore aims to fill this gap by exploring the role nonfinancial support systems play in triggering SMEs' collaborations and innovativeness in Europe. We show that non-financial support (framework condition) significantly facilitates collaboration and innovation of European SMEs, by using partial least squares structural equation modelling (PLS-SEM) and 216 sampled datasets of the 27 EU countries from 2012 to 2020 European Innovation Scoreboard (EIS). Our expectation was confirmed about the SMEs' collaboration significant effects on their innovative activities, which subsequently translate into innovative outputs. We also found indirect significant effect of the non-financial support on SME's innovation output. This study serves several practical implications and contributes to the ongoing debate on the effects of non-financial support for cooperation and innovation activities of European SMEs.
Nový pohled na analýzu inovativní podpory evropských malých a středních podniků: Záleží na nefinanční podpoře?
Keywords: Innovative support; analysis; EU; Non -financial support; Financial support; SME; Inovativní podpora; analýza; EU; Nefinanční podpora; Finanční podpora; MSP